Smart port - Khadzri, Shadiq; Saad, Muhammad Syazni Aiman; Yusi, Atiqah Al-Insyirah Hamdan; Othman, Siti Nur Hidayah; Sheikh Abdul Mutalib, Siti Khairunnisa (Universiti Teknologi MARA, Kedah, 2019)
Nowadays, smartphone is an important item for everyone. Normally, students use smartphone in their daily routine, unfortunately the battery of the smartphone will be easily drain and it cause a problem among students. Smart Port helps to solve this problem as it provides the powerbank renting service. This invention is align with the implementation of digital library that is rapidly growth in Malaysia. Digital library is a collection of documents in organized electronic form, available on the Internet or on CD-ROM disks. User may access to the articles of magazines, books, papers, images, sound files, and videos. If the invention such as "smart-port" is provided in the library specifying on academic library, thus it will help students to access all the information and latest feed. This helps the effort of the library in order to attract the users to come and visit the library. This invention helps the library to gain profit as it is a fee based service. User needs to pay and borrow at least a book before the renting service. It supports the book lending practices. There is an ad such as news pop out on their smartphone before they access the the free internet provided. This encourages reading habit among students. As a conlusion, this invention is beneficial for both library and the students since the vision of “Smart Port” is align with the mission and vision of the library in supporting the reading culture.